With a pinch of salt: The importance of history in evaluation of hyponatremia (Indian Journal of Case Reports, 2021)
Fatigue, a non-specific symptom, is often dismissed as trivial or functional, however, an underlying malignant, endocrine, or metabolic disorder may be the cause of fatigue. We present the case of an elderly lady who presented with tiredness, anorexia, and vomiting for a month. Physical examination revealed pallor, facial puffiness, and coarse crackles in the left mammary area. Investigations revealed hyponatremia and hypokalemia. The patient denied a history of amenorrhea and lactation failure, but further questioning revealed that she had severe post-partum hemorrhage necessitating a hysterectomy. Investigations revealed normal TSH, low normal fT4, inappropriately low FSH, and LH. The patient was treated with thyroid and adrenal hormone replacement. We present this case to emphasize the importance of detailed history taking for a medical diagnosis, especially in conditions like Sheehan’s syndrome with relatively non-specific presenting complaints.